Enhancing the Transparency of Student Merit System Using QR Code Technology: A Smart Campus Initiative (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technology has led to the utilization of information systems into human daily life activities. Computer systems have helped improve the modern human lifestyle by simplifying and facilitating activities from listening to music, grocery shopping to communicating with peoples across the world. Gearing up to smart campus initiatives, one of the issues to be tackled was the transparency in validating the student’s attendance system used in many campuses and university events. The employment of technologies such as QR Code and facial recognition to validate the student’s attendance certainly have helped in addressing this issue. In order to ensure the transparency of the existing manual student merit system used in the campus, this paper presents a solution known as CyberScan QR Code for Student Merit System that allows the students to obtain merits by scanning QR codes, as well as allowing student councils to provide merits for any events by generating QR codes. Students can keep track of their current total merit points and the events that they have previously attended so if there are any problems regarding their merits, they can always refer to their history of attended events as evidence. This paperless solution merit system also helps to reduce the usual time taken to calculate a huge amount of merits thus preventing from any miscalculation. Clearly, this initiative creates not just an efficient, transparent service but another greater experience for students to feel connected academically and socially.